The Quakers: LGBTIQ+ Activism and Institutional Cohesion - Boland, Joshua (Journal for the academic study of religion, 2021)
Liberal Quakerism’s engagement with the public sphere acts as a mechanism for producing social solidarity within the movement. This argument is demonstrated through an examination of Quaker engagement with Queer social issues in the UK, US and Australia. The social activism of Quakers sustains their identity as a liberal religious organisation sympathetic to progressive causes and nurtures a sense of common purpose within the movement that subsumes internal differences. It is argued that, while Quaker orthopraxis within the Society binds internal diversity together, this can also include Friends’ activist engagement with the secular world. This focus on the dialectical relationship between Quakerism’s internal culture and external social processes suggest that a dynamic relationship exists between contemporary secularism and liberal religious groups.